Sesi Interaktif Peningkatan Regulasi Emosi Anak di MI Walisongo Paesan 01 Pekalongan - Rizqoh Muawannah; Muhammad Rifa'i Subhi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIM Sinjai, 2025)
Childhood is the key period of how he will run his life in the future. Therefore, the provision of emotion regulation skills in children is important to create their involvement in daily life. Ways of expression and self-control, both socially, emotionally and cognitively are needed. In this research, tasawuf and psychotherapy-based empowerment activities were carried out which focused on improving children's emotional regulation through interactive sessions. This empowerment activity aims to increase children's awareness in recognizing and managing emotions. The method used is Service Learning, applying the theory that has been learned in class in real activities in the community. This activity targets 4th grade students of MI Walisongo Paesan 01, Kedungwuni, Pekalongan, with interactive sessions that include initial assessment, delivery of material on recognizing and managing emotions, case studies, followed by reflection. Students were actively involved in discussion and reflection on their emotion management. The interactive session on improving emotion regulation showed students' progress in identifying different types of emotions, relating emotions to certain circumstances, and providing examples of appropriate emotion regulation.